Impact Of Financing Restructuring And Foreclosed Collateral On Non-Performing Financing Levels In The Covid-19 Era - Anisa Nur Fitriyanti; Mufti Arief Arfiansyah (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2023)
The Covid-19 pandemic has impacted the banking sector, including the increase in problematic financing. This research aims to show the impact of restructuring financing and foreclosed collateral (RFFC) on non-performing financing (NPF) levels during the Covid-19 pandemic. This research uses a quantitative approach. The population of this research is Islamic commercial banks (ICB). The research sample was taken using a purposive sampling technique, so a research sample of 6 ICB was obtained in three years, namely 2020-2022. This research uses data analysis in the form of multiple linear regression analysis using the Eviews application. The research results show that financing restructuring and RFFC each positively and significantly affect NPF. This research can be used as reading material related to banking economics and inform banks that success in implementing policies to minimize problematic financing requires good cooperation between banks and customers.